Removing barriers for citizen participation to urban innovation. - Wolff, Annika; Gooch, Daniel; Cavero, Jose; Rashid, Umar; Kortuem, Gerd (Springer Open, 2019)
The potential of open data as a resource for driving citizen-led urban innovation relies not only on a suitable technical infrastructure but also on the skills and knowledge of the citizens themselves. In this chapter, the authors describe how a smart city project in Milton Keynes, UK, is supporting multiple stages of citizen innovation, from ideation to citizen-led smart city projects. The Our MK initiative provides support and funding to help citizens develop their ideas about making their communities more sustainable into reality. This approach encounters challenges when engaging with citizens in identifying and implementing data-driven solutions to urban problems. The majority of citizens have little practical experience with the types of data sets that might be available or possess the appropriate skills for their analysis and utilisation for addressing urban issues or finding novel ways to hack their city. The authors go on to describe the Urban Data School, which aims to offer a long-term solution to this problem by providing teaching resources around urban data sets aimed at raising the standard of data literacy amongst future generations. Lesson resources that form part of the Urban Data School have been piloted in one primary and three secondary schools in Milton Keynes. This work has demonstrated that with the appropriate support, even young children can begin to develop the skills necessary to work with large complex data sets. Through these two approaches, the authors illustrate some of the barriers to citizen participation in urban innovation and detail these solutions to overcoming those barriers. Scaffolding community initiatives through creating flexible formulas anchored in social media channels that are easy to appropriate and adapt are presented as a promising avenue to investigate further.
Keywords: Stadtsoziologie; Digitale Medien; Partizipation; Stadtgesellschaft; Stadtgestaltung; Interaktion; Open Data; Schule; Big Data